Respuesta :

Answer:

(x - 1)(3x - 5)

Step-by-step explanation:

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x-term.

product = 3 × 5 = 15 and sum = - 8

The factors are - 3 and - 5

use these factors to split the middle term

3x² - 3x - 5x + 5 ( factor the first/second and third/fourth terms )

= 3x(x - 1) - 5(x - 1) ( take out the common factor (x - 1) )

= (x - 1)(3x - 5)


Answer:

(x - 1)(3x - 5)

ACCESS MORE